Antecedents of Audit Report Lag with Audit Quality as a Moderator - Herawaty, Vinola; Nugraha, Maulindieta Alvia (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
This study aims to test and determine the effect of key audit matters, audit tenure, financial distress, operational complexity, and gender chief executive officer (CEO) on audit report lag with audit quality as a moderator. This study uses secondary data collected from the Indonesia Stock Exchange (IDX), the Ministry of Finance Information and Documentation Management Officer (PPID Kemenkeu), and the official website of each company. This quantitative research uses multiple linear regression analysis with the research population: consumer non-cyclical companies with food and beverages and pharmaceutical subsectors in 2019-2022 that publish annual and audited financial reports. The research population was 35 companies, and it was found that 31 companies met the research criteria in a 4-year period, with a total of 124 research samples and 12 data affected by outliers. Therefore, the total research sample is 112 companies. The results of hypothesis testing in this study indicate that financial distress and company operational complexity significantly positively affect audit report lag. While key audit matters, audit tenure, gender CEO, and audit quality do not affect audit report lag. Also, it has been proven that audit quality could weaken the relationship between financial distress and audit report lag. However, audit quality cannot moderate between key audit matters, audit tenure, operational complexity, and chief executive officer gender with audit report lag. This study implies that investors may take into consideration audit report lag before deciding to invest in a company.